The predictive value of CatLet© angiographic scoring system for long-term prognosis in patients with acute myocardial infarction presenting > 12 h after symptom onset - Wang, Heng; He, Yi; Fan, Jia-Li; Li, Xu; Zhou, Bing-Yuan; Jiang, Ting-Bo; He, Yong-Ming (Frontiers in Cardiovascular Medicine, 2022)
Background We have recently developed the Coronary Artery Tree description and Lesion EvaluaTion (CatLet©) angiographic scoring system, which is capable of accounting for the variability in coronary anatomy, and risk-stratifying patients with coronary artery disease. This study aimed to clarify whether the CatLet score had a predictive value for long-term prognosis in patients with acute myocardial infarction (AMI) presenting > 12 h after symptom onset. Materials and methods The CatLet score was calculated for 1,018 consecutively enrolled AMI patients, who were divided into 3 groups according to the CatLet score tertiles. The primary endpoint was major adverse cardiac events (MACEs), defined as a composite of myocardial infarction, cardiac death, and ischemia-driven revascularization; secondary endpoints were all-cause death, cardiac death, myocardial infarction, and ischemia-driven revascularization. Results The CatLet score was capable of predicting long-term prognosis at a median 4.9-year follow-up alone or after adjustment for risk factors. Multivariable-adjusted hazard ratios (95% CI)/unit higher score were 1.06 (1.05–1.08) for MACEs, 1.05 (1.03–1.07) for all-cause death, 1.06 (1.04–1.09) for cardiac death, 1.06 (1.04–1.08) for myocardial infarction, and 1.06 (1.04–1.08) for revascularization. The univariate model showed good calibration (χ2 = 8.25, P = 0.4091) and good discrimination (area under ROC curve = 0.7086) for MACEs. Conclusion The CatLet score is an independent predictor of long-term clinical outcomes of patients with AMI presenting > 12 h after symptom onset (http://www.chictr.org.cn; Registry Number: ChiCTR2000033730).